EFFECT OF DAUHRUDAVASTHA (DESIRES DURING PREGNANCY) ON FETAL DEVELOPMENT - Pradnya Ravindra, Deshpande; Prabhakharrao, Pande Prasad; Suvarna Rambhau, Sonawane; Chandrakant, Shahane Vijay (International Journal of Ayurveda and Pharma Research, 2015)
Life begins with conception even nine months prior to the delivery. Entire gestational period is important for achievement of healthy baby along with prevention of complications during pregnancy. Dauhrudavastha is the special concept of Ayurveda affecting fetal growth. It is the period during which pregnant woman (Dauhrudini) expresses dietary and behavioural desires. These longings are desires of fetus, fulfillment of which is beneficial for proper gestation, whereas non fulfillment or ignorance causes various developmental anomalies. In present clinical study, impact of fulfillment of longings of Garbhini (pregnant woman) on fetal growth is assessed. For this, 60 pregnant women were selected. They were grouped on the basis of questionnaire especially prepared for case study. 30 pregnant women who developed Dauhrudavastha and longings were attended and fulfilled registered in group A. Group B involves 30 pregnant women whose longings were ignored. Entire gestational period (up to delivery) is observed during ANC check up. After delivery, gestational ages of neonates were assessed by examining physical and neurological parameters. On comparison of Dauhrudavastha and neonatal examination, it was found that 80% neonates of group A having appropriate at term gestational age. Only 23.33% neonates of group B were having appropriate at term gestational age. The study suggests that along with nutritional support, attention should be given to Dauhrudavastha as it affect fetal growth.